The homes in the COVID-19 era. How their use and values are changing - Signorelli, Carlo; Capolongo, Stefano; D'Alessandro, Daniela; Fara, Gaetano Maria (Acta Biomedica Atenei Parmensis, 2020)
The long lockdown, the frequent adoption of smart working, the online lessons for both school and university pupils, and the domestic isolation of many people in order to stop the spread of the SARS-CoV-2, have changed the way millions of people lived their home spaces in the last few months. This also led to a backlash on real estate values, enhancing some characteristics and penalizing others.